Research and solving some equations in the ring of residue classes - Valeriu BORDAN; Mihaela HAJDEU (Acta et Commentationes, Sciences of Education, 2025)
In this paper are investigated some equations in the ring of residue classes. It is shown that these equations possess a single solution only in the ring of residue classes modulo 5. It is shown that the compatibility of these equations in the ring structure is related to the pairs of consecutive mutually invertible elements in these rings.